Dalumat ng Inang Bayan at ang Pananaw ni Andres Bonifacio sa Kababaihan (The Concept of the Motherland and Andres Bonifacio’s Perspective on Women) - Rodriguez-Tatel, Mary Jane (Social Sciences and Development Review, 2013)
The Katipunan was in their discourse of Nation the metaphor of a Mother – “Inang Bayan.” This intelligent conversation was a response of the “anak ng bayan” in the written discussion of Madre España expanded by the Filipino Ilustrado. The ideology in the discourse of Inang Bayan is inherent to all members of Katipunan. This ideology united the Katipuneros to search for the “kagalingan ni Inang Bayan.” In the final analysis, the Katipunan gave a high preference to define the word nation as the “mother” vis-a vis the “patria” of the west, the value and honor given by the supremo to women. It’s good to engage the question, why character of a woman was used by the anak ng bayan to conceptualize the katipunan organization. This research will try to answer this question by presenting the following: first, the socio-cultural context that was responsible in the promulgation of such discourse; second, the perspective of Andres Bonifacio who was the proponent of the said discourse as brain for interpretation.